Green composite flocculant, preparation method and application thereof
Patent Information
- Application Number
- CN202611389475.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-08
- Publication Date
- 2026-10-23
AI Technical Summary
[0003]然而,在有机污染污水体系中,有机物常吸附或包覆于胶体颗粒与悬浮颗粒表面,产生空间位阻效应,增强胶体体系稳定性,削弱絮凝剂的处理效果
1.原料绿色经济,实现废弃物资源化:本发明以农业废弃物香蕉皮为主要原料之一,经简单碱改性即可使用,来源广泛、成本低廉,既降低絮凝剂生产成本,又实现农业废弃物的高值化利用,环境友好。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention belongs to the fields of water treatment agents and sludge dewatering technology, specifically relating to a green composite flocculant, its preparation method and application, and particularly to a composite flocculant based on alkali-modified banana peel powder, guar gum and polyaluminum chloride, and its application in organic wastewater treatment and sludge dewatering. Background Technology
[0002] With socio-economic development, water pollution has become increasingly prominent, severely restricting sustainable development and threatening ecological security. Therefore, water pollution control, advanced wastewater treatment, and water reuse are of significant practical importance. Coagulation / flocculation is one of the core units of water treatment processes, widely used in water supply treatment, wastewater treatment, industrial wastewater treatment, and sludge dewatering. Flocculants can promote the aggregation and sedimentation of fine particles, colloidal substances, suspended organic matter, and some colloidal pollutants in water through double-layer compression, adsorption neutralization, adsorption bridging, and netting / sweeping, thereby reducing water turbidity, color, and some COD, and improving solid-liquid separation efficiency.
[0003] However, in organic wastewater systems, organic matter often adsorbs or coats the surface of colloidal and suspended particles, creating a steric hindrance effect that enhances the stability of the colloidal system and weakens the treatment effect of flocculants. In sludge systems, extracellular polymers, humic substances, and organic matter form stable hydrated structures, resulting in loose sludge flocs and poor dewatering performance. Relying solely on traditional inorganic coagulants or synthetic polymeric flocculants such as polyacrylamide generally suffers from insufficient treatment efficiency and high operating costs.
[0004] Furthermore, while existing synthetic flocculants offer good treatment results, they also pose certain environmental risks and limitations in application. For example, polyacrylamide is widely used in sludge dewatering and industrial wastewater treatment, but it is difficult to degrade, and residual acrylamide monomers pose toxicity and carcinogenic risks, hindering the resource utilization and ecological safety of treated sludge. Even with composite modification to reduce its dosage, it is still difficult to completely avoid the problems of high molecular weight residues and secondary pollution.
[0005] In summary, current technologies still lack a green composite flocculant that has a wide range of raw material sources, low cost, environmental friendliness, and can effectively treat organic polluted wastewater and replace polyacrylamide for sludge dewatering. Summary of the Invention
[0006] The technical problem to be solved by the present invention is to overcome the shortcomings of the prior art and provide a green composite flocculant, its preparation method and application, which achieves efficient flocculation through the synergistic effect of ternary components, and is both environmentally friendly and economical, and can replace polyacrylamide for sewage treatment and sludge dewatering.
[0007] The technical solution adopted to solve the above-mentioned technical problems is: a green composite flocculant and its preparation method and application, including alkali-modified banana peel powder, guar gum and polyaluminum chloride; the alkali-modified banana peel powder is banana peel powder modified by alkaline solution, used as an organic matter adsorption material and floc skeleton material; the guar gum is used as a natural polymer adsorption bridging material; the polyaluminum chloride is used as an inorganic coagulant.
[0008] Further, the mass ratio of the alkali-modified banana peel powder, guar gum and polyaluminum chloride is 1:0.005-0.5:0.1-10; preferably, the mass ratio is 1:0.01-0.2:0.2-5.
[0009] Furthermore, the alkali-modified banana peel powder has a particle size of less than 100 mesh, and its surface has active functional groups such as hydroxyl, carboxyl, and phenolic hydroxyl groups, as well as a rough porous structure.
[0010] Secondly, the present invention provides a method for preparing the above-mentioned green composite flocculant, comprising the following steps: S1. The banana peel powder is subjected to alkali modification treatment to obtain alkali-modified banana peel powder; S2. Alkali-modified banana peel powder, guar gum, and polyaluminum chloride are mixed evenly to obtain a green composite flocculant.
[0011] Further, in step S1, the preparation method of the banana peel powder is as follows: wash and cut the banana peel into pieces, dry it at 50-60℃ for 10-20 hours, pulverize it and pass it through a 100-mesh sieve.
[0012] Further, in step S1, the alkali modification treatment specifically involves: adding banana peel powder to an alkaline solution for reaction, performing solid-liquid separation after the reaction, washing the solid until the washing liquid is neutral or near-neutral, and then drying, grinding, and passing it through a 100-mesh sieve.
[0013] Further, the alkaline solution is a sodium hydroxide solution, a potassium hydroxide solution, or a mixture of the two, and the concentration of the alkaline solution is 0.05-2.0 mol / L; the solid-liquid ratio of banana peel powder to alkaline solution is 1:5-1:50 g / mL; the alkaline modification reaction temperature is 20-80℃, the reaction time is 0.5-8h; and the drying temperature is 50-60℃.
[0014] Thirdly, the present invention provides the application of the above-mentioned green composite flocculant in replacing polyacrylamide in the treatment of organic polluted wastewater or in the dewatering of sludge.
[0015] Furthermore, the organic polluted wastewater is wastewater containing humic acid, colloidal particles, suspended particles, natural organic matter, chromatic substances, or colloidal COD, including but not limited to water influent from water supply plants with high permanganate index, domestic sewage, secondary treatment effluent from urban sewage, industrial organic wastewater, or wastewater containing suspended organic matter.
[0016] Furthermore, the sludge is residual sludge from urban wastewater treatment plants, industrial sludge, sludge containing organic matter, and other sludge that requires dewatering treatment.
[0017] The mechanism of action of this invention is as follows: Alkali-modified banana peel powder has a surface rich in active functional groups such as hydroxyl, carboxyl, and phenolic hydroxyl groups, and possesses a rough pore structure and biomass framework. It can efficiently adsorb humic acid, dissolved organic matter, and colloidal organic matter in water, weakening the stabilizing effect of organic matter on colloidal particles. Simultaneously, it can act as a solid framework to strengthen the floc structure. Guar gum, a natural high-molecular-weight long-chain substance, is rich in hydroxyl groups and can act as an adsorption bridging agent between multiple micro-flocs, increasing floc particle size, improving floc strength, and sedimentation performance. Polyaluminum chloride hydrolyzes to form cationic aluminum hydroxyl species, which reduce the electrostatic repulsion of particles through charge neutralization and promote pollutant aggregation and floc formation through a net-like sweeping action.
[0018] During sludge dewatering, alkali-modified banana peel powder can adsorb humic substances and some extracellular polymers in the sludge, and act as a skeletal material to improve the filter cake structure. Polyaluminum chloride neutralizes the negative charges on the surface of sludge particles and extracellular polymers, compresses the electric double layer, and disrupts the hydration structure. Guar gum promotes the aggregation of sludge micro-flocs through long-chain bridging, forming large, compact, and more easily dewatered sludge flocs. The synergistic effect of these three components can achieve sludge dewatering effects comparable to polyacrylamide, while avoiding the environmental risks of synthesizing polymers.
[0019] The beneficial effects of this invention are as follows: 1. Green and economical raw materials, realizing the resource utilization of waste: This invention uses banana peels, agricultural waste, as one of the main raw materials. It can be used after simple alkali modification. It is widely available and inexpensive, which not only reduces the production cost of flocculants, but also realizes the high-value utilization of agricultural waste, which is environmentally friendly.
[0020] 2. Ternary synergistic flocculation with excellent treatment effect: This invention constructs a multi-mechanism synergistic system of "organic matter adsorption-charge neutralization instability-polymer bridging-skeleton reinforcement", which can effectively solve the problem of decreased flocculation efficiency caused by organic matter coating colloids and improve the treatment effect of organic polluted wastewater.
[0021] 3. Can replace polyacrylamide and reduce environmental risks: This invention uses natural high-molecular-weight guar gum to replace synthetic high-molecular-weight polyacrylamide to play a bridging role. Combined with the skeletal support of banana peel powder and the charge neutralization effect of polyaluminum chloride, the sludge dewatering effect is comparable to that of polyacrylamide, which is conducive to the subsequent resource utilization of sludge.
[0022] 4. Wide range of applications and simple and easy process: The composite flocculant of this invention can be used for coagulation and clarification of various organic polluted wastewater, as well as for sludge dewatering and conditioning; the preparation process only involves two steps: alkali modification and mixing, which is simple to operate, requires no complicated equipment, and is easy to scale up for production and engineering application. Detailed Implementation
[0023] To make the technical problems, technical solutions, and beneficial effects of this application clearer, the following detailed description is provided in conjunction with the embodiments. Unless otherwise defined, all technical terms used herein have the same meaning as understood by one of ordinary skill in the art. It should be understood that the following embodiments are for illustrative purposes only and should not be construed as limiting the scope of protection of this invention.
[0024] This invention provides a green composite flocculant based on banana peel, guar gum, and polyaluminum chloride, along with its preparation method and applications. Alkali-modified banana peel powder, guar gum, and polyaluminum chloride are compounded to prepare a green composite flocculant that is inexpensive, environmentally friendly, and exhibits excellent flocculation performance. This composite flocculant can be used for the treatment of organically polluted wastewater, particularly suitable for wastewater containing humic acid, natural organic matter, colloidal particles, suspended particles, chromogenic substances, or colloidal COD. Furthermore, this composite flocculant can also be used for sludge dewatering, replacing the use of synthetic polymeric flocculant PAM.
[0025] The core of this invention lies in the organic combination of alkali-modified banana peel powder, guar gum, and polyaluminum chloride to construct a multi-mechanism synergistic flocculation system that integrates organic matter adsorption, colloidal instability, floc skeleton support, polymer bridging, and net-like sweeping effects. Alkali-modified banana peel powder, obtained from banana peel through pretreatment and alkali modification, possesses hydroxyl, carboxyl, phenolic hydroxyl, aromatic structures, and a rough porous structure on its surface, making it suitable as both an organic matter adsorbent and a floc skeleton material. Guar gum, a natural polymer with a long-chain structure and abundant hydroxyl groups, can play an adsorption bridging role between multiple micro-flocs. Polyaluminum chloride, as an inorganic coagulant, hydrolyzes in water to form cationic aluminum hydroxyl species and aluminum hydroxide flocs, promoting pollutant aggregation and sedimentation through adsorption charge neutralization, adsorption bridging, and net-like sweeping effects. When the three work synergistically, alkali-modified banana peel powder preferentially adsorbs humic acid, dissolved organic matter, and colloidal organic matter in the water, weakening the stabilizing effect of organic matter on colloidal particles; polyaluminum chloride further destabilizes colloidal particles and forms micro-flocs; guar gum connects multiple micro-flocs through long-chain bridging, increasing the floc size, strengthening the structure, and accelerating sedimentation.
[0026] Compared with existing technologies, the present invention differs in that: existing technologies mostly use a compound of polyaluminum chloride and PAM, relying mainly on the polymeric bridging effect of PAM to enhance the flocculation effect. However, PAM has problems such as being difficult to degrade, having toxic residual monomers, and limiting the resource utilization of sludge. Some technologies also use plant powders or plant extracts as flocculants, but most of them only utilize the adhesive or soluble polymeric components of plant materials, resulting in a single function and failing to fully utilize their potential. The present invention does not simply mix plant powder with inorganic coagulants, but rather removes soluble sugars, organic acids, pigments, waxes, and surface impurities from banana peel powder through alkali modification treatment, fully exposing the fiber skeleton and functional groups, making it more suitable as an organic matter adsorption material and floc skeleton material. At the same time, guar gum is used instead of PAM to exert the polymeric bridging effect, which works synergistically with the charge neutralization and net-catching sweeping effects of polyaluminum chloride to achieve efficient clarification of organic polluted wastewater.
[0027] Specifically, the preparation method of the green composite flocculant based on banana peel, guar gum, and polyaluminum chloride includes the following steps: (1) Preparation of banana peel powder: The banana peels used in this invention can be waste banana peels from commercially available bananas, and there are no special restrictions on the variety or origin. After removing any remaining pulp from the banana peels, wash them thoroughly with water to remove surface dirt, sugar, and other impurities. Then cut them into small pieces and dry them in an oven at 50-60℃ for 10-20 hours. After drying, pulverize them using a pulverizer or grinder and pass them through a 100-mesh sieve to obtain banana peel powder.
[0028] In a preferred embodiment, the banana peel powder particle size is controlled to be around 100 mesh. If the particle size is too large, the contact area between the banana peel powder and organic pollutants and colloidal particles in the water is small, which is detrimental to the adsorption of organic matter and subsequent floc formation; if the particle size is too small, the material easily forms fine suspended particles, which may increase the turbidity of the effluent and affect the solid-liquid separation effect. Therefore, passing the banana peel powder through a 100-mesh sieve can balance adsorption contact area, dispersibility, and subsequent sedimentation performance.
[0029] (2) Preparation of alkali-modified banana peel powder: Take the banana peel powder obtained in step (1) and add it to an alkaline solution for alkali modification treatment. The alkaline solution is sodium hydroxide solution, potassium hydroxide solution or a combination thereof. The concentration of the alkaline solution is 0.05-2.0 mol / L; the solid-liquid ratio of banana peel powder to alkaline solution is 1:5-1:50 g / mL; the alkali modification temperature is 20-80℃; and the alkali modification time is 0.5-8h. After the modification treatment, solid and liquid are separated by centrifugation, filtration or vacuum filtration, and the solid is repeatedly washed with deionized water or tap water until the washing liquid is neutral or near neutral. Then, the obtained solid is dried at 50-60℃, ground and passed through a 100-mesh sieve to obtain alkali-modified banana peel powder.
[0030] In a preferred embodiment, the alkaline solution is a sodium hydroxide solution. Alkali modification treatment can remove soluble sugars, organic acids, pigments, waxes, and other surface impurities from banana peel powder, reducing the risk of releasing soluble organic matter into water bodies during use. Simultaneously, alkali treatment can roughen the surface structure of the banana peel powder, exposing the biomass skeleton structures such as cellulose, hemicellulose, and lignin, making it easier for oxygen-containing functional groups such as hydroxyl, carboxyl, and phenolic hydroxyl groups to participate in the adsorption of humic acids, soluble organic matter, and colloidal organic matter.
[0031] When the alkaline solution concentration is too low, its effect on removing impurities from the surface of banana peel powder and exposing the fiber skeleton is not significant, making it difficult to fully improve its adsorption and skeleton support properties. When the alkaline solution concentration is too high, it will cause excessive damage to some organic skeleton structures in the banana peel powder, leading to a decrease in material strength, fine powdering, or loss of oxygen-containing functional groups. If the alkali modification time is too short, the modification is insufficient; if the alkali modification time is too long, it will cause excessive hydrolysis of the material structure. Therefore, this invention controls the alkaline solution concentration, solid-liquid ratio, modification temperature, and modification time within the above-mentioned ranges to obtain alkali-modified banana peel powder that has both adsorption and skeleton support properties.
[0032] (3) Preparation and compounding method of composite flocculant: The alkali-modified banana peel powder obtained in step (2) is mixed with guar gum and polyaluminum chloride at a mass ratio of 1:0.005-0.5:0.1-10 to obtain a green composite flocculant based on banana peel, guar gum and polyaluminum chloride. Preferably, the alkali-modified banana peel powder, guar gum and polyaluminum chloride are compounded at a mass ratio of 1:0.01-0.2:0.2-5.
[0033] Regarding the compounding ratio of alkali-modified banana peel powder, guar gum, and polyaluminum chloride, if the proportion of alkali-modified banana peel powder is too low, its adsorption of organic matter and skeletal support will be insufficient, making it difficult to effectively weaken the stabilizing effect of organic matter on colloidal particles. If the proportion of alkali-modified banana peel powder is too high, it may increase the content of suspended solids in the water and adversely affect the turbidity of the effluent. If the proportion of guar gum is too low, the bridging effect between microflocs will be insufficient; if the proportion of guar gum is too high, colloidal protection may be formed. If the proportion of polyaluminum chloride is too low, the charge neutralization and netting / sweeping effects will be insufficient; if the proportion of polyaluminum chloride is too high, it may cause charge reversal, increase residual aluminum, or increase reagent costs. Therefore, only within the compounding ratio range specified in this invention can a good synergistic flocculation effect be achieved among the three components.
[0034] (4) Application in organic polluted wastewater: When the green composite flocculant of the present invention is used for the treatment of organic polluted wastewater, the organic polluted wastewater may be wastewater containing humic acid, colloidal particles, suspended particles, natural organic matter, color substances or colloidal COD, including but not limited to water inlet of water supply plants with high permanganate index, domestic sewage, secondary treatment effluent of urban sewage, industrial organic wastewater or wastewater containing suspended organic matter.
[0035] (5) Application in sludge dewatering: The green composite flocculant described in this invention can also be used for sludge conditioning and dewatering. The sludge can be residual sludge from urban sewage treatment plants, industrial sludge, sludge containing organic matter, or other sludge. When used for sludge dewatering, polyaluminum chloride can neutralize the negative charge on the surface of sludge particles and extracellular polymers, thereby disrupting the sludge hydration structure; alkali-modified banana peel powder can adsorb humic substances, colloidal organic matter, and some extracellular polymers in the sludge, while also serving as a solid skeleton material to improve the filter cake structure; guar gum can promote the aggregation of sludge micro-flocs through long-chain bridging, forming sludge flocs with larger particle size, more stable structure, and easier dewatering.
[0036] The green composite flocculant prepared and used by the above method has the advantages of inexpensive raw materials, environmental friendliness, stable treatment effect, and wide application range. Through the synergistic effect between alkali-modified banana peel powder, guar gum, and polyaluminum chloride, it can effectively solve the problem of decreased flocculation efficiency caused by organic matter coating colloidal particles, and can replace polyacrylamide in wastewater flocculation and sludge dewatering.
[0037] The following specific embodiments will be provided to explain the solution of the present invention. Those skilled in the art will understand that the following embodiments are for illustrative purposes only and should not be considered as limiting the scope of the invention. Where specific techniques or conditions are not specified in the embodiments, they are performed according to conventional techniques in the art or according to the product instructions. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.
[0038] In the following embodiments, the bananas used were purchased from the market and are common species of bananas.
[0039] In the following examples, the sodium hydroxide used was of analytical grade and was purchased from Sinopharm Chemical Reagent Co., Ltd.
[0040] In the following examples, the polyaluminum chloride used was of analytical grade and purchased from Xi'an Tianmao Baoding Biotechnology Co., Ltd.
[0041] In the following examples, the kaolin used was purchased from Sinopharm Chemical Reagent Co., Ltd.
[0042] In the following examples, the humic acid used was purchased from Shanghai Maclean Biochemical Technology Co., Ltd.
[0043] In the following embodiments, the organic polluted wastewater used is kaolin-humic acid simulated organic polluted wastewater, and the specific preparation process is as follows: Weigh 1.0 g of humic acid, add a small amount of 0.1 mol / L NaOH solution to aid dissolution, stir thoroughly, adjust the pH to 7.0 ± 0.2 with 0.1 mol / L HCl, and bring the volume to 1 L with ultrapure water to obtain a 1 g / L humic acid mother liquor. Weigh 10.0 g of kaolin particles, add ultrapure water and bring the volume to 1 L, stir thoroughly to disperse, and obtain a 10 g / L kaolin mother liquor.
[0044] When preparing simulated organic wastewater, humic acid mother liquor was added to ultrapure water to achieve a final humic acid concentration of 20 mg / L. Then, kaolin mother liquor was added, and the turbidity of the system was adjusted to 200 NTU. After adjusting the pH to 7.0 ± 0.2, the mixture was stirred at room temperature for 30-60 minutes to ensure sufficient contact between the humic acid and kaolin particles, thus obtaining simulated organic wastewater with an initial turbidity of 200 NTU and a humic acid concentration of 20 mg / L. Example 1
[0045] The preparation of alkali-modified banana peel powder includes the following steps: (1) Take fresh banana peels and wash them repeatedly with ultrapure water to remove surface dirt, pulp residue, and soluble impurities. Cut the washed banana peels into small pieces and dry them in an oven at 60°C for 12 hours. After drying, pulverize them using a pulverizer and pass them through a 100-mesh sieve to obtain banana peel powder.
[0046] (2) Weigh 5.0g of the above banana peel powder and add it to 100mL of 0.5mol / L NaOH solution. Place the mixture in a constant temperature shaker and react at 60℃ and 150rpm for 2h.
[0047] (3) After the alkali modification is completed, solid-liquid separation is performed by centrifugation, and the supernatant is discarded. The obtained solid is repeatedly washed with ultrapure water until the pH of the washing solution is 7.0. Then the washed solid is placed in a 60℃ oven to dry to constant weight, ground, and passed through a 100-mesh sieve again to obtain alkali-modified banana peel powder.
[0048] After the above treatment, soluble sugars, organic acids, pigments, waxes and surface impurities in banana peel powder are removed, and the exposure of its surface fiber skeleton and oxygen-containing functional groups is increased, so it can be used as a subsequent organic matter adsorption material and floc skeleton material. Example 2
[0049] The preparation of green composite flocculants includes the following steps: The alkali-modified banana peel powder obtained in Example 1 was mixed with guar gum and polyaluminum chloride at a mass ratio of 1:0.02:0.4 to obtain a green composite flocculant based on banana peel, guar gum and polyaluminum chloride.
[0050] Among them, alkali-modified banana peel powder is used to adsorb humic acid, colloidal organic matter, and suspended organic matter in water, and serves as a floc skeleton material; guar gum is used to exert the bridging effect of natural high-molecular long chains; and polyaluminum chloride is used to exert the effects of charge neutralization, adsorption bridging, and netting and sweeping. The synergistic effect of the three can effectively improve the flocculation and sedimentation of organic polluted wastewater. Example 3
[0051] Green composite flocculant treatment of kaolin-humic acid simulated organic polluted wastewater.
[0052] Take 500 mL of kaolin-humic acid simulated organic polluted wastewater and place it in a beaker. The initial turbidity of the simulated organic polluted wastewater is 200 NTU and the humic acid concentration is 20 mg / L.
[0053] Performance testing: 50 mg of the green composite flocculant prepared in Example 2 was added to the simulated organic polluted wastewater, making the dosage 100 mg / L. The mixture was stirred at 150 rpm for 15 min. After stirring, the mixture was allowed to settle for 10 min, and the turbidity was measured. The turbidity removal efficiency reached 98.8%. Example 4
[0054] Effects of different compounding ratios and dosages on the treatment effect of green composite flocculants To investigate the effects of the compounding ratio of alkali-modified banana peel powder, guar gum, and polyaluminum chloride, and the total dosage of the composite flocculant on the treatment effect of organic polluted wastewater, the mass ratio of guar gum to alkali-modified banana peel powder, the mass ratio of polyaluminum chloride to alkali-modified banana peel powder, and the total dosage of the composite flocculant were used as the factors to be investigated. The L9(3)24-2400 ppm method was employed. 3 Optimization was carried out through orthogonal experiments.
[0055] In this experiment, the relative mass fraction of alkali-modified banana peel powder was fixed at 1. Factor A was the mass ratio of guar gum to alkali-modified banana peel powder, Factor B was the mass ratio of polyaluminum chloride to alkali-modified banana peel powder, and Factor C was the total dosage of the composite flocculant. The orthogonal experimental factors and levels are shown in Table 1.
[0056] Table 1. Factor Levels of Orthogonal Experiment
[0057] Each group took 500 mL of kaolin-humic acid simulated organic polluted wastewater and placed it in a beaker. The initial turbidity of the simulated organic polluted wastewater was 200 NTU and the humic acid concentration was 20 mg / L.
[0058] Table 2 Results of orthogonal experiment on the ratio and dosage of composite flocculant
[0059] According to the mass ratios shown in Table 2, the alkali-modified banana peel powder, guar gum, and polyaluminum chloride prepared in Example 1 were compounded. After the green composite flocculant was added, the mixture was continuously stirred at 150 rpm for 15 min. After stirring, the mixture was allowed to settle for 10 min, and the turbidity of the supernatant was measured. Three parallel samples were set up for each group of experiments, and the turbidity removal rate was taken as the average of the three measurements. The orthogonal experimental design and measurement results are shown in Table 2.
[0060] A range analysis was performed on the experimental results in Table 2. The average and range of turbidity removal rates for each factor at different levels are shown in Table 3.
[0061] Table 3. Range analysis results of orthogonal experiment on composite flocculant ratio
[0062] As shown in Tables 2 and 3, within the experimental range examined in this embodiment, the mass ratio of polyaluminum chloride to alkali-modified banana peel powder has the greatest impact on turbidity removal, followed by the mass ratio of guar gum to alkali-modified banana peel powder. The total dosage of the composite flocculant has a relatively small impact. Based on the average turbidity removal rate at different levels of each factor, the preferred combination is A2B2C2, i.e., the mass ratio of alkali-modified banana peel powder, guar gum, and polyaluminum chloride is 1:0.02:0.4, and the total dosage of the composite flocculant is 100 mg / L. Example 5
[0063] Green composite flocculants are used for sludge dewatering.
[0064] Sludge from a laboratory-run, long-term stable SBR reactor was used as the sludge to be treated. Specific resistance (SRF) of the sludge was used to evaluate its filtration and dewatering performance.
[0065] Performance testing: 50 mg of the green composite flocculant prepared in Example 2 was added to the sludge to be treated, making the dosage 100 mg / L, and the change in sludge SRF was measured. The results showed that the SRF of the conditioned sludge decreased from 2.47 × 10⁻⁶ mg / L. 12 m / kg decreased to 1.04×10 12 The concentration of sludge was reduced by 57.89% (m / kg), significantly improving the dewatering efficiency of the sludge. Comparative Example 1
[0066] Polyaluminum chloride alone is used to treat organic polluted wastewater.
[0067] The only difference from Example 3 is that no green composite flocculant is added; instead, the same mass of polyaluminum chloride powder as in Example 3 is used as the flocculant. All other operating conditions are the same as in Example 3.
[0068] Performance testing: Polyaluminum chloride powder was added to the simulated organic wastewater, and the mixture was stirred at 150 rpm for 15 minutes. After stirring, the mixture was allowed to settle for 10 minutes, and the turbidity was measured. The turbidity removal efficiency reached 86.7%.
[0069] As shown in Comparative Example 1, the turbidity removal efficiency of the conventional flocculant polyaluminum chloride for organic polluted wastewater is much lower than that in Example 3, indicating that the green composite flocculant can significantly improve the flocculation effect on organic polluted wastewater. Comparative Example 2
[0070] PAM is used alone for sludge dewatering.
[0071] The only difference from Example 5 is that no green composite flocculant is added; only PAM is used as the flocculant. All other operating conditions are the same as in Example 5.
[0072] Performance testing: PAM was added to the sludge to be treated, and the change in sludge SRF was measured. The results showed that the SRF of the conditioned sludge increased from 2.47 × 10⁻⁶ to 2.47 × 10⁻⁶. 12 m / kg decreased to 1.07×10 12 m / kg, a decrease of 56.68%.
[0073] As shown in Comparative Example 2, the green composite flocculant of the present invention can improve the sludge dewatering performance through the synergistic effects of polyaluminum chloride charge neutralization, alkali-modified banana peel powder adsorption and skeleton support, and guar gum long-chain bridging. Its treatment effect can reach the same level as PAM and is conducive to reducing the environmental risks caused by PAM residue. Comparative Example 3
[0074] A binary compound system lacking guar gum is used to treat organic polluted wastewater.
[0075] The only difference from Example 3 is that guar gum is not added to the flocculant used; it consists only of alkali-modified banana peel powder and polyaluminum chloride. All other experimental conditions and proportions are the same as in Example 3.
[0076] Performance testing: The composite flocculant was added to simulated organic polluted wastewater and stirred at 150 rpm for 15 min. After stirring, the mixture was allowed to settle for 10 min, and the turbidity was measured. The turbidity removal efficiency reached 90.2%.
[0077] In this binary system, alkali-modified banana peel powder can adsorb some humic acid and colloidal organic matter, and participate in floc construction as a solid framework material. Polyaluminum chloride can promote the instability of colloidal particles and the formation of micro-flocs through charge neutralization, adsorption bridging, and net-trapping sweeping. However, due to the lack of the natural high-molecular-weight long-chain bridging effect of guar gum in the system, the formed micro-flocs are difficult to further connect to form flocs with larger particle size, stable structure, and good settling performance, resulting in some fine flocs remaining in the supernatant. Therefore, the turbidity removal efficiency of this binary system is significantly lower than that of the ternary compound system in Example 3, indicating that guar gum plays an important role in promoting micro-floc aggregation, increasing floc particle size, and improving settling performance. Comparative Example 4
[0078] There is a lack of binary compound systems for treating organic polluted wastewater using alkali-modified banana peel powder.
[0079] The only difference from Example 3 is that the flocculant used does not contain alkali-modified banana peel powder, but consists only of guar gum and polyaluminum chloride. All other experimental conditions are the same as in Example 3.
[0080] Performance testing: The composite flocculant was added to simulated organic wastewater and stirred at 150 rpm for 15 minutes. After stirring, the mixture was allowed to settle for 10 minutes, and the turbidity was measured. The turbidity removal efficiency reached 89.6%.
[0081] In this binary system, polyaluminum chloride can reduce the electrostatic repulsion between colloidal particles through charge neutralization and promote the formation of micro-flocs through net-trapping and sweeping effects. Guar gum can utilize its natural long-chain polymer structure to connect multiple micro-flocs, promoting floc formation. However, due to the lack of alkali-modified banana peel powder in the system, it cannot preferentially remove or fix humic acid and colloidal organic matter in the water through adsorption. Humic acid can still adsorb or coat the surface of kaolin particles and micro-flocs, generating steric hindrance and enhancing the stability of the colloidal system. At the same time, the lack of solid framework support provided by alkali-modified banana peel powder limits the structural strength and sedimentation performance of the formed flocs. Therefore, the turbidity removal efficiency of this binary system is significantly lower than that of the ternary compound system in Example 3, indicating that alkali-modified banana peel powder plays an important role in weakening the colloidal stabilizing effect of organic matter and constructing the floc framework. Comparative Example 5
[0082] There is a lack of binary compound systems for treating organic polluted wastewater using polyaluminum chloride.
[0083] The only difference from Example 3 is that the flocculant used does not contain polyaluminum chloride, but is composed only of alkali-modified banana peel powder and guar gum. All other experimental conditions are the same as in Example 3.
[0084] Performance testing: The composite flocculant was added to simulated organic polluted wastewater and stirred at 150 rpm for 15 min. After stirring, the mixture was allowed to settle for 10 min, and the turbidity was measured. The turbidity removal efficiency reached 80.3%.
[0085] In this binary system, alkali-modified banana peel powder can adsorb some humic acid and colloidal organic matter, and act as a floc skeleton material; guar gum can play a certain adsorption bridging role through its long-chain structure. However, due to the lack of polyaluminum chloride in the system, it cannot fully neutralize the negative charges on the surfaces of kaolin particles, humic acid, and other colloidal substances, nor can it effectively compress the colloidal double layer and promote colloidal instability through entrapment and sweeping. With the colloidal particles still exhibiting strong electrostatic repulsion, guar gum struggles to form effective bridges between particles, and the collision and binding efficiency between alkali-modified banana peel powder and pollutants is also limited. Therefore, the turbidity removal efficiency of this binary system is significantly lower than that of the ternary compound system in Example 3, and lower than that of the binary system lacking guar gum or alkali-modified banana peel powder. This indicates that the charge neutralization, double-layer compression, and entrapment and sweeping effects of polyaluminum chloride are crucial for the instability of colloidal particles and subsequent floc formation.
[0086] The results of Example 3 and Comparative Examples 1, 3, 4, and 5 show that while using polyaluminum chloride alone or in a binary compound system composed of any two components can reduce the turbidity of simulated organic wastewater to some extent, their treatment effects are lower than those of the ternary compound system composed of alkali-modified banana peel powder, guar gum, and polyaluminum chloride. These results indicate that the treatment effect of the ternary compound system of this invention is not a simple summation of the effects of each component, but rather the result of a synergistic effect among the three components. The embodiments of the present invention have been described in detail above, but the present invention is not limited thereto. Within the scope of knowledge possessed by those skilled in the art, various changes can be made without departing from the spirit of the present invention.
Claims
1. A green composite flocculant, characterized in that, The mixture includes alkali-modified banana peel powder, guar gum, and polyaluminum chloride; the alkali-modified banana peel powder is banana peel powder modified by an alkaline solution and is used as an organic adsorbent and floc skeleton material; the guar gum is used as a natural polymer adsorbent bridging material; and the polyaluminum chloride is used as an inorganic coagulant.
2. The green composite flocculant according to claim 1, characterized in that, The mass ratio of the alkali-modified banana peel powder, guar gum, and polyaluminum chloride is 1:0.005-0.5:0.1-10.
3. The green composite flocculant according to claim 2, characterized in that, The preferred mass ratio of alkali-modified banana peel powder, guar gum, and polyaluminum chloride is 1:0.01-0.2:0.2-5.
4. The green composite flocculant according to claim 1, characterized in that, The alkali-modified banana peel powder has a particle size of less than 100 mesh and its surface has hydroxyl, carboxyl, and phenolic hydroxyl functional groups and a rough porous structure.
5. A method for preparing the green composite flocculant according to any one of claims 1-4, characterized in that, Includes the following steps: S1. The banana peel powder is subjected to alkali modification treatment to obtain alkali-modified banana peel powder; S2. Alkali-modified banana peel powder, guar gum, and polyaluminum chloride are mixed evenly to obtain a green composite flocculant.
6. The preparation method according to claim 5, characterized in that, In step S1, the banana peel powder is prepared by washing and cutting the banana peel into pieces, drying it at 50-60℃ for 10-20 hours, pulverizing it, and then passing it through a 100-mesh sieve.
7. The preparation method according to claim 6, characterized in that, In step S1, the alkali modification treatment specifically involves: adding banana peel powder to an alkaline solution for reaction, performing solid-liquid separation after the reaction, washing the solid until neutral, drying, grinding, and then passing it through a 100-mesh sieve.
8. The preparation method according to claim 7, characterized in that, The alkaline solution is a sodium hydroxide solution, a potassium hydroxide solution, or a mixture of the two, with a concentration of 0.05-2.0 mol / L; the solid-liquid ratio of banana peel powder to the alkaline solution is 1:5-1:50 g / mL; the alkaline modification reaction temperature is 20-80℃, the reaction time is 0.5-8h; and the drying temperature is 50-60℃.
9. The application of the green composite flocculant of claim 1 in treating organic polluted wastewater or in sludge dewatering as a substitute for polyacrylamide.
10. The application according to claim 9, characterized in that, The organic polluted wastewater is wastewater containing humic acid, colloidal particles, suspended particles, natural organic matter, chromatic substances, or colloidal COD, including water influent with a high permanganate index, domestic sewage, secondary treatment effluent of urban sewage, industrial organic wastewater, or wastewater containing suspended organic matter. The sludge is residual sludge from urban sewage treatment plants, industrial sludge, or sludge containing organic matter.